Synergistic Integration and Pharmacomechanical Function of Enzyme‐Magnetite Nanoparticle Swarms for Low‐Dose Fast Thrombolysis. Issue 34 (29th July 2022) - Tang, Xiuzhen; Manamanchaiyaporn, Laliphat; Zhou, Qi; Huang, Chenyang; Li, Lihuang; Li, Ziqiao; Wang, Longchen; Wang, Jienan; Ren, Lei; Xu, Tiantian; Yan, Xiaohui; Zheng, Yuanyi
Abstract: Magnetic micro‐/nanoparticles are extensively explored over the past decade as active diagnostic/therapeutic agents for minimally invasive medicine. However, sufficient function integration on these miniaturized bodies toward practical applications remains challenging. This work proposes a synergistic strategy via integrating particle functionalization and bioinspired swarming, demonstrated by recombinant tissue plasminogen activator modified magnetite nanoparticles (rtPA‐Fe3 O4 NPs) for fast thrombolysis in vivo with low drug dosage. The synthesized rtPA‐Fe3 O4 NPs exhibit superior magnetic performance, high biocompatibility, and thrombolytic enzyme activity. Benefiting from a customized magnetic operation system designed for animal experiments and preclinical development, these agglomeration‐free NPs can assemble into micro‐/milli‐scale swarms capable of robust maneuver and reconfigurable transformation for on‐demand tasks in complex biofluids. Specifically, the spinning mode of the swarm exerts focused fluid shear stresses while rubbing on the thrombus surface, constituting a mechanical force for clot breakdown. The synergy of the NPs' inherent enzymatic effect and swarming‐triggered fluid forces enables amplified efficacy of thrombolysis in an in vivo occlusion model of rabbit carotid artery, using lower drug concentration than clinical dosage. Furthermore, swarming‐enhanced ultrasound signals aid in imaging‐guided treatment. Therefore, the pharmacomechanical NP swarms herein represent an injectable thrombolytic tool joining advantages of intravenous drug therapy and robotic intervention. Abstract : An injectable thrombolytic tool for fast thrombolysis in vivo using low drug dosage is reported, highlighting synergistic pharmacomechanical function of integrated enzyme‐magnetite (rtPA‐Fe3 O4 ) nanoparticle swarms in rabbit carotid artery.